Morphology and zoogeography of the burrower-like gammarid Gammarus koshovi (Bazikalova, 1946) (Crustacea, Amphipoda, Gammaridae) – An overlooked and poorly known species in the Siberian fauna - Sidorov, Dmitry; Yalysheva, Elena; Sharyi-Ool, Mariana (European Journal of Taxonomy, 2021)
A comprehensive survey of several lakes in the Tuva Republic of Russia yielded, besides the ubiquitous Gammarus lacustris, the discovery of a small freshwater, lacustrine amphipod not previously recorded in this area. A comparative study of the Tore-Khol Lake gammarid population, probably conspecific with Gammarus koshovi (Bazikalova, 1946) originating from Khubsugul Lake, was conducted. The species, G. koshovi, is characterized by a specific habitus: a small-sized compact body, all limbs shortened, carpi of pereopods (PIII and PIV) reduced, coxal plates broad, and pereopod dactyli sturdy. It has been suggested that juveniles of the euryoecious G. lacustris or other large species could be confused with the relatively small G. koshovi. Consequently, we decided to present the distribution of gammarid species throughout south Siberia and Mongolia, referring to the sequences of works primarily by Soviet authors, which may be hard to access by international readers. We discuss affinity with related groups, distribution, and ecology of G. koshovi to better understand their evolution. Additionally, the zoobenthic species diversity of widely represented groups in the ecosystems of Tore-Khol Lake is briefly reviewed. An identification key for the Siberian Gammarus with 10 species is provided.